(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
The molecular structure and vibrational spectra of Furfural Semicarbazone (FSC) have been calculated with the help of density fuctional theory (DFT) using 6-31++G(d,p) and 6-311++G(d,p) basis sets.Â The solid phase FT-IR and FT-Raman spectra of furfural semicarbazone have been recorded in the range 4000-400cm-1 and 4000-100 cm-1, respectively.Â On the basis of B3LYP calculations, the normal coordinate analysis has been performed to assign the vibrational fundamental frequencies according to potential energy distribution. The optimum molecular geometry, harmonic vibrational frequencies, infrared intensities and Raman Scattering activities were calculated by density functional theory (DFT/B3LYP) method with 6-31++G(d,p) and 6-311++G(d,p) basis sets. The difference between the observed and scaled wave number values of most of the fundamentals is very small.Â Stability of the molecule arising from hyper conjugative interactions, charge delocalization have been analyzed using Natural Bond Orbital (NBO) analysis. The electro dipole moment (Î¼) and first hyperpolarizability (Î²) values of the investigated molecule are computed using Scaled Quantum Mechanical Force field (SQMF) method.Â Besides, HOMO and LUMO analysis and Fukui functions of the title molecule have also been calculated using DFT method.